Study on the Clutch Fuzzy Adaptive Control Technology of AMT during Start Process - Liu Ziyun; Liu Zijian; Pi Haojie; Ai Yandi; Zhou Jinchao (Jixie chuandong)
Aiming at the key issues of the clutch wear serious,the vehicle has great impact caused by clutch inaccurate control in the starting control of automatic mechanical transmission（ AMT）,taking the AMT clutch as the study object and reducing the impact degree and friction work as goal,a new kind of clutch engagement controlling strategy based on fuzzy control and self- adaptive control method is proposed. First,some uncertain parameters of clutch control are analyzed by using fuzzy control method,and then with the input parameters as the object,the fuzzy control rules is modified by the adaptive control theory. Through comparing different control effects between fuzzy controller and fuzzy adaptive controller,the validity of this controlling strategy is verified. The results show that,the fuzzy adaptive control is more accurate and effective than fuzzy control during start process by simulation and experiment,the impact intensity,friction work and friction plate wear of clutch can be reduced some extent,And the driving performance is significantly improved.